التأهيل التربوي المبكر (التدخل المبكر) لأطفال ذوي متلازمة داون وأسرهم - البيرق علي (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This research aims to shed light on the concept of educational qualification early for children with Down syndrome because of its great importance in the rehabilitation of these children and help them to training and education, which could believe them integration opportunities and social adjustment with those around them from the rest of the other segments of society. This research deals with the concept of early rehabilitation (early intervention), objectives, principles and rules upon which the educational qualification process with the elements and components of the rehabilitation program and to clarify the need for rehabilitation and its importance with the address to a number of intervention models, and research found a number of proposals and recommendations which are useful for the rehabilitation of children with Down and his family and working on the mental abilities. يهدف هذا البحث إلى القاء الضوء على مفهوم التأهيل التربوي المبكر لأطفال ذوي متلازمة داون نظراً لما له من أهمية كبيرة في تأهيل هؤلاء الأطفال ومساعدتهم على التدريب والتعليم مما قد يؤمن لهم فرص الدمج والتكيف الاجتماعيين مع من حولهم من باقي فئات المجتمع الأخرى . تناول هذا البحث مفهوم التأهيل المبكر (التدخل المبكر) وأهدافه والأسس والقواعد التي تقوم عليها عملية التأهيل التربوي مع عناصر ومكونات برنامج التأهيل وتوضيح ضرورة التأهيل وأهميته مع التطرق إلى عدد من نماذج التدخل, وخَلُصَ البحث إلى جملة من المقترحات والتوصيات التي تفيد في تأهيل طفل الداون واسرته وتعمل على تنمية قدراته العقلية .